Mission to impregnate “soul” in a hoe: Between the Christian Cruise and the Kurusu - Platzeck Senra, Letícia Larin (2019)
A digression between two cross-shaped liturgical objects captures different ways of relating to time and space. The contrast between aspects imbued in the treatment with the Christian cruise and the «kurusu» - which indicates graves of Guarani-Kaiowá Amerindians relatives and ancestors - reveals different ways in which the body copes with the surrounding reality. How to evade the current prevailing logic, that generates oppressive scenarios such as the existing in the state of Mato Grosso do Sul, Brazil, where Guarani-Kaiowá barely survive? To seek for some resolutive inspiration, the present reflection endeavors to devise ways to immerse itself in the Indigenous worldview. As a proposal, the individual performs an effort to be intrigued by the “skin permeability”, that is, to be aware of the significant “distractions” introduced in the present. This behavior is thus understood as a way of feeling ecologically and socially, sustainable and responsible.